Carbon nanotube uptake changes the biomechanical properties of human lung epithelial cells in a time-dependent manner1. Issue 19 (21st May 2015) - Dong, Chenbo; Eldawud, Reem; Sargent, Linda M.; Kashon, Michael L.; Lowry, David; Rojanasakul, Yon; Zoica Dinu, Cerasela
<x xml:space="preserve">Abstract</x> The toxicity of engineered nanomaterials in biological systems depends on both the nanomaterial properties and the exposure duration.